Continuing formation process of physical education teachers in inclusive educational context - Cruz, Gilmar de Carvalho; Ferreira, Júlio Romero (Brazilian journal of physical education and sport, 2005)
The aims of this study were to track how Physical Education teachers deal with students with special needs and to understand how a continuing education program may contribute to cope the challenges related with the inclusion process. The research was based on the focalization group methodological suppositions. Sixteen Physical Education teachers of the public educational system of Londrina constituted the Study/Work Group focusing on the issues related to the intervention of the Physical Education teacher in inclusive school environments. The meetings were carried out every other week during the years 2002 and 2003. Data collection was carried out by means of: collective interviews, observation and analysis of classes recorded in VHS, and reflective field diaries. The treatment given to the data collected included Group photography, radiography, and cinematography. The results indicated important oppositions to be overcome in the school environment - the opposition between theory and practice for instance - reflecting on the educational assistance given by teachers of Physical Education to students with special needs. Final considerations suggest procedures related to the implementation of continuing formation programs as well as the accomplishment of research in a relational perspective in educational contexts that intend to be inclusive.